2018
DOI: 10.14236/ewic/hci2018.60
|View full text |Cite
|
Sign up to set email alerts
|

Generational Differences in Password Management Behaviour

Abstract: Passwords still remain a very common authentication method for online accounts. Many studies have investigated people's risky password management behaviour, including reusing passwords, writing them down, and sharing them with others. However, most studies provide limited information about the demographics of their participants. There may be substantial differences in password management behaviour between younger and older people, as they represent very different generations with different experiences of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…On the other hand, the implementation of password hygiene training programmes for youth (13-16 years) show changes in password-setting behaviour [15]. Researchers found that there is a high percentage of reused passwords in both groups of older and younger respondents [16]. The researchers emphasise that public campaigns about password security have not been successful, as the problem continues to exist.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, the implementation of password hygiene training programmes for youth (13-16 years) show changes in password-setting behaviour [15]. Researchers found that there is a high percentage of reused passwords in both groups of older and younger respondents [16]. The researchers emphasise that public campaigns about password security have not been successful, as the problem continues to exist.…”
Section: Related Workmentioning
confidence: 99%
“…A number of other studies have also found that age is less important that might be expected in relation to online security [2,15]. However, other studies have found age differences [16,25], although both these studies were about password-related behaviour in particular, with both showing that younger people were more likely to undertake at least some risky password behaviours.…”
Section: Introductionmentioning
confidence: 96%
“…According to [9], the implementation of password hygiene training programmes for youth (13-16 years) show changes in password-setting behaviour. Studies have shown that there is a high percentage of reused passwords in younger adults [10], [11]. Likewise, while older adults are keen to protect themselves, they do feel anxiety (e.g., fear of forgetting the password), they nd password management cumbersome and time-consuming, hence they engage in the culture of password reused [9], [12].…”
Section: Introductionmentioning
confidence: 99%